The Effects of Parenthood During Graduate School on PhD Recipients' Paths to the Professoriate: A Focus on Motherhood. Issue 176 (December 2016) - Kulp, Amanda M.
Abstract : This chapter focuses on graduate students who are parents, the career‐related resources they gather during graduate school, and the influence of those resources on PhD‐earning mothers' attainment of tenure‐track faculty jobs at U.S. higher‐education institutions.